Indonesian Export Analysis: Autoregressive Distributed Lag (ARDL) Model Approach - Syarifah Labibah; Abd. Jamal; Taufiq C. Dawood (Universitas Hayam Wuruk Perbanas, 2020)
There are some factors predicted tohave an effect on the countries’ economic devlopment. This study aimed to analyze the long-term and short-term effects of In-flation, Exchange Rate, and Foreign Economic Growth (the destination of the United States, China, and Japan) on the Indonesian Export. The Auto-Regressive Distributed Lag (ARDL) Model is used in this analysis from 1968 through 2017. The results of the analysis show that in the long-term, the inflation and the economic growth in China as well in Japan has a positive sign and significant effect on Indonesian exports. In addition, in the short-term, the US exchange rate and economic growth have a positive significant effect on Indonesian exports.